COVID-19 challenge: proactive management of a Tertiary University Hospital in Veneto Region, Italy. (17th August 2020) - Carretta, Giovanni; Contessa, Cristina; Boemo, Deris Gianni; Bordignon, Greta; Bennici, Silvia Eugenia; Merigliano, Stefano; Boschetto, Margherita; Capizzi, Alfio; Cattelan, Annamaria; Causin, Francesco; Cianci, Vito; Flor, Luciano; et al.
ABSTRACT: Background: The aim of this study is to describe the successful emergency plan implemented by Padova University Hospital (AOUP) during the COVID-19 pandemic. Methods: The emergency plan included early implementation of procedures aimed at meeting the increasing demand for testing and care while ensuring safe and timely care of all patients and guaranteeing the safety of healthcare workers. Results: From 21 February to 1 May 2020, there were 3, 862 confirmed cases of SARS-CoV-2 infection in the Province of Padua. A total of 485 patients were hospitalized in AOUP, of which 91 were admitted to the ICU; 12 .6% of admitted patients died. The average bed occupancy rate in the ICU was 61.1% (IQR 43.6%:77.4%). Inpatient surgery and inpatient admissions were kept for 76% and 74%, respectively, compared to March 2019. A total of 123, 077 swabs were performed, 19.3% of which (23, 725 swabs) to screen AOUP workers. The screening of all staff showed that 137 of 7, 649 (1.8%) hospital workers were positive. No healthcare worker died. Discussion: AOUP strategy demonstrated effective management of the epidemic thanks to the timely implementation of emergency procedures, a well-coordinated effort shared by all hospital Departments, and their continuous adjustment to the ongoing epidemic. Timely screening of all hospital workers proved to be particularly important to defend the hospital, avoiding epidemic clusters due to unknown positive cases.